Prevalence of chronic hepatitis B infection among residents of hilly tribal district in northern India - Barall, Deepesh; Gupta, Anmol; Sharma, Brij; Mazta, Salig R.; Singh, Sudhir (International Journal Of Community Medicine And Public Health, 2018)
Background: Viral hepatitis B is a systemic infection affecting predominantly the liver, caused by hepatitis B virus. The similarity of hilly tribal’s in spiti and the Tibetans with documented high prevalence of HBsAg encouraged us to explore the burden of the hepatitis B infection in them as well. So the study was designed to document the prevalence of the chronic hepatitis B infection for timely intervention with the required prevention and control measures. Methods: 30 cluster villages from the 82 inhabitated villages were taken with 37 samples from each cluster village. Data was collected using interview schedule. Serum samples were taken and subjected to sandwich ELISA for the detection of HBsAg and positive samples were tested for the HBeAg then after. Results: The study included 1110 participants with 424 males. 99.7% of them were Buddhist and 98.5% belonged to Scheduled Tribe category. 60.1% were educated up to the middle and18% were illiterates. The prevalence of HBsAg was 21.9% (CI 19.6-24.6) with 22.6% in females and 20.9% in males. HBeAg was positive in 24.4% of HBsAg positive cases, higher in the 15-24 years age group and 30.5% in the reproductive females. Conclusions: The current study has reported hyper endemic (21.9%) sero-prevalence of HBsAg with infectivity rate of 24.4%, more in the young and reproductive population. The infection is homogenously distributed among the Buddhist tribal population in the study area.